Clinical Goals and Barriers to Effective Psoriasis Care - Bruce E. Strober; Joelle M. van der Walt; April W. Armstrong; Marc Bourcier; Andre V. E. Carvalho; Edgardo Chouela; Arnon D. Cohen; Claudia de la Cruz; Charles N. Ellis; Andrew Y. Finlay; Alice B. Gottlieb; Johann E. Gudjonsson; et al. (Adis, Springer Healthcare, 2018)
Abstract Engaging global key opinion leaders, the International Psoriasis Council (IPC) held a day-long roundtable discussion with the primary purpose to discuss the treatment goals of psoriasis patients and worldwide barriers to optimal care. Setting clear expectations might ultimately encourage undertreated psoriasis patients to seek care in an era in which great gains in therapeutic efficacy have been achieved. Here, we discuss the option for early treatment of all categories of psoriasis to alleviate disease impact while emphasizing the need for more focused attention for psoriasis patients with mild and moderate forms of this autoimmune disease. In addition, we encourage policy changes to keep pace with the innovative therapies and clinical science and highlight the demand for greater understanding of treatment barriers in resource-poor countries.